Effect of substrate temperature on structural and linear and nonlinear optical properties of nanostructured PLD a-SiC thin films. (December 2016) - Dey, Partha P.; Khare, Alika
Graphical abstract: Highlights: Nanostructured a-SiC of different stochiometry have been fabricated by PLD. Shift in stochiometry from Si-rich to nearly stochiometric SiC with increasing Ts . Stochiometry dependent tunable optical bandgap in a-SiC. Films showed self focusing and reverse saturation absorption under cw He-Ne laser. Optical χ (3) obtained was 10 7 times than that of reported in bulk SiC crystal. Abstract: In this paper, the effect of substrate temperatures (Ts ) on the structural, linear and non-linear optical properties of nanostructured amorphous Silicon Carbide (a-SiC) thin films deposited onto fused silica by pulsed-laser deposition technique is reported. The structural and compositional properties were studied by X-ray diffraction, Raman spectroscopy and Fourier transform Infrared spectroscopy. A transition from Silicon-rich SiC to nearly stoichiometric SiC was observed with increasing Ts . The absorption coefficient (α), refractive index (n), optical band gap and thickness of the films were determined from UV–vis-IR spectra. Static refractive indices of the films were found to vary from 2.99–2.54 with the increasing Ts . The optical band gap of the films was found to be increasing from 1.5 eV to 2.33 eV with increase in Ts . The third order non-linear optical susceptibility ( χ (3) ) of the a-SiC thin films estimated from Z-scan studies was found to be of the order of 10 −3 esu.